Treatment of immune thrombocytopenia (ITP) secondary to malignancy: a systematic review - Podda, Gian Marco; Fiorelli, Elisa M.; Birocchi, Simone; Rambaldi, Benedetta; Di Chio, Maria Chiara; Casazza, Giovanni; Cattaneo, Marco (Platelets (Edinburgh), 2022)
Immune thrombocytopenia (ITP) can be associated with lymphoproliferative diseases (LPD) or solid tumors. A systematic review of published literature was conducted to evaluate response to treatment of ITP secondary to malignancy. Primary outcome was overall response (complete response+response) to first-line treatments [steroids alone or in combination with intravenous immunoglobulins (IVIg)]. Among secondary outcomes, overall response to second-line treatments [splenectomy, rituximab or thrombopoietin receptor agonists (TPO-RA)] and death were evaluated. Of the retrieved 238 text articles, 108 were analyzable, for a total of 154 patients: 142 in 105 case reports and 12 in 3 observational studies. Thirty-nine patients had solid tumors, 114 LPD, and 1 both. The median follow up was 19 months (IQR, 9-40). The overall response was 50% (62% in solid tumors, 46% in LPD) after steroids and 47% (67% in solid tumors, 36% in LPD) after steroids+IVIg, which are lower than historical responses observed in primary ITP (≈80%). The overall responses to rituximab (used in LPD only), splenectomy and TPO-RA (70%, 73% and 92%, respectively) were similar to those observed in primary ITP. Seven patients (6%) died due to bleeding events. ITP secondary to malignancy appears to be associated with unsatisfactory response to first-line treatments.